Wounds Difficult to Heal: An Effective Treatment Strategy - Capoano, Raffaele; Businaro, Rita; Tesori, Maria C.; Donello, Claudia; Lombardo, Federica; Lo Vasco, Vincenza Rita; Capriotti, Lorena; Corsi, Mariangela; Di Raimo, Tania; Leopizzi, Martina; Salvati, Bruno; Ricci, Serafino (Current Vascular Pharmacology, 2017)
Objective: Treatment of wounds difficult to heal concerns 50% of the elderly population in Italy and is therefore a relevant social burden. The present study shows how the treatment with autologous leuco-platelets reduces the healing time of wounds improving the functional recovery. Patients and Methods: Patients (n=100) with ulcers of the legs were divided in two groups: 1) 50 patients treated with conventional therapies; 2) 50 patients treated with autologous leuco-platelet concentrate (LPC) and hyaluronic acid (HIAFF, Hyalofill-F® ) as a scaffold. Results: After 2 months, a 49% reduction in wound area was observed in the second group and in about 65% wound reduction was achieved in 15 days (4 LPC dressings). In contrast, patients treated by conventional therapies, showed a longer healing time and a greater percentage of failures. Morphometric analysis of biopsy samples obtained from the edge as well as from the bottom of the lesions obtained from the LPC group, detected an abundant presence of neoformed capillaries, characterized by a cubic,
Keywords: morphometry